A review of robotic-assisted laparoscopic partial nephrectomy in the management of renal duplication anomalies - Batra, Nikhil Varun; Dangle, Pankaj (Frontiers in Surgery, 2024)
Open and purely laparoscopic partial nephrectomy or heminephrectomy has been the standard management for renal duplication anomalies for symptomatic children with non-functional renal moieties. While robotic-assisted laparoscopic partial nephrectomy (RALPN) has been established as a safe and feasible option for the management of renal duplex anomalies, there remains a paucity of data on this topic. The aim of this study is to comprehensively review all available outcomes data and update the use of emerging technologies in robotic surgery which continue to make RALPN a viable and advantageous option in the management of renal duplex anomalies.